Macromolecular crystallography and biology at the Linac Coherent Light Source - Sandra Mous; Mark S. Hunter; Frédéric Poitevin; Sébastien Boutet; Leland B. Gee (Journal of Synchrotron Radiation)
The Linac Coherent Light Source (LCLS) has significantly impacted the field of biology by providing advanced capabilities for probing the structure and dynamics of biological molecules with high precision. The ultrashort coherent X-ray pulses from the LCLS have enabled ultrafast, time-resolved, serial femtosecond crystallography that is inaccessible at conventional synchrotron light sources. Since the facility's founding, scientists have captured detailed insights into biological processes at atomic resolution and fundamental timescales. The ability to observe these processes in real time and under conditions closely resembling their natural state is transforming our approach to studying biochemical mechanisms and developing new medical and energy applications. This work recounts some of the history of the LCLS, advances in biological research enabled by the LCLS, key biological areas that have been impacted and how the LCLS has helped to unravel complex biological phenomena in these fields.